Variation in PARK10 is not associated with risk and age at onset of Parkinson's disease in large clinical cohorts - Simón-Sánchez, Javier; Heutink, Peter; Gasser, Thomas (Neurobiology of aging, 2015)
A recent study in autopsy-confirmed Parkinson's disease (PD) patients and controls revived the debate about the role of PARK10 in this disorder. In an attempt to replicate these results and further understand the role of this locus in the risk and age at onset of PD, we decided to explore NeuroX genotyping and whole exome sequencing data from 2 large independent cohorts of clinical patients and controls from the International Parkinson's Disease Genomic Consortium. A series of single-variant and gene-based aggregation (sequence kernel association test and combined multivariate and collapsing test) statistical tests suggested that common and rare genetic variation in this locus do not influence the risk or age at onset of clinical PD.